2005
DOI: 10.1080/15614260500047143
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary education, commitment, and turnover in police work

Abstract: This study investigated the effects of tertiary education on police turnover (separations) and job attitudes. It is sometimes argued that tertiary education will reduce the commitment of police to staying in the job because they will experience frustrated promotional aspirations and they possess greater employment mobility. In a case study of Queensland police officers with between five and nine years of service, human resource data showed no significant differences in turnover rates for degree holders and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
(39 reference statements)
0
16
0
Order By: Relevance
“…Winfree et al (1997) confirmed this lack of association, as did a recent Australian examination (Jones et al 2005). Carlan's (1999) survey of criminal justice graduates revealed higher satisfaction for those with master's degrees, but concluded that enhanced satisfaction was actually the product of criminal justice employment more so than education (no job satisfaction differences for those employed in a criminal justice capacity).…”
Section: Educationmentioning
confidence: 82%
“…Winfree et al (1997) confirmed this lack of association, as did a recent Australian examination (Jones et al 2005). Carlan's (1999) survey of criminal justice graduates revealed higher satisfaction for those with master's degrees, but concluded that enhanced satisfaction was actually the product of criminal justice employment more so than education (no job satisfaction differences for those employed in a criminal justice capacity).…”
Section: Educationmentioning
confidence: 82%
“…While previous research has analyzed officers" education and turnover decisions (Jones, Jones, & Prenzler, 2006), research has failed to analyze whether officers" training impacts their decisions to leave or transfer. This research assumes that if officers" education and training are positively related to performance, the existence of a large number of officers with limited training and education should produce a performance issue that incumbent officers find difficult to ignore.…”
Section: Education and Trainingmentioning
confidence: 99%
“…Unlike most existing research on police officer turnover intentions focusing on the correlates or predictors (Adams & Buck, 2010;Brunetto & Farr-Wharton, 2003;Drew et al, 2008;Jones, Jones, & Prenzler, 2005;Matz et al, 2014;Rivera, 2011), Brough and Frame (2004) and Allisey et al (2014) investigated turnover process using survey data collected from New Zealand police officers and U.K. police officers, respectively. Both studies proposed the turnover process model, consisting of three categories of antecedents to actual turnover: distal factors including personal characteristics and working conditions, job satisfaction as a mediating factor, and turnover intention as the most proximal indicator of actual turnover (Allisey et al, 2014;Brough & Frame, 2004).…”
Section: Turnover Process Modelmentioning
confidence: 99%
“…Unlike most existing research on police officer turnover intentions focusing on the correlates or predictors (Adams & Buck, 2010; Brunetto & Farr-Wharton, 2003; Drew et al., 2008; Jones, Jones, & Prenzler, 2005; Matz et al., 2014; Rivera, 2011), Brough and Frame (2004) and Allisey et al. (2014) investigated turnover process using survey data collected from New Zealand police officers and U.K. police officers, respectively.…”
Section: Turnover Process Modelmentioning
confidence: 99%